5G-V2X-Based Vehicle Charging Station Planning Method Considering Different Land-Use Types - Ke XIONG; Siyu WU; Haina ZHENG; Rui WANG; Yu ZHANG (Zhongguo dianli)
With the development of the 5G technology, much progress has been made in vehicle to everything (V2X) and the Internet of Vehicle. Mobile users could quickly obtain relevant physical facility information, and facility operators could better allocate scheduling resources based on the road network information. In the city planning, different area has different functions. From the view of electrical vehicle, two area will own the same characteristic in the arriving distribution if they belong to the same function. In addition, the grid capacity, land restriction, cost and price will have similar patterns. Based on the area characteristics and the V2X assistance, the station network model was proposed in this paper. Concerning about the aim of commercial charging network, we optimize the charging station network within a giving area with the objective of retained profits and the constraints of grid capacity and land. A charging network strategy which is on the basis of station parameter and parking distribution is devised. The strategy includes two parts, the first part calculates the optimal charger number in the given station; the second part removes and aggregates some candidate station to optimal the charging network station. The M/M/S/K queue model and user charging intention curve are introduced to picture the user behavior in charging station. The impacts of critical parameters of charging network on the system performance is provided.